The revising of the Tangney Self‐Control Scale for Chinese students. Issue 2 (4th May 2016) - Unger, Alexander; Bi, Chongzeng; Xiao, Ying‐Ying; Ybarra, Oscar
Abstract : Recent studies have characterized self‐control as a vital psychological variable that helps explain various problems. Tangney's Self‐Control Scale (SCS) is a self‐report measurement to assess individual differences in traits of self‐control. It has gained popularity in social and psychological science research. In China, there are a few Chinese‐version scales measuring general self‐control, which can be applied to college students. The purposes of the present study were to evaluate: (a) the psychometric properties of the Chinese version of Tangney's SCS using confirmatory factor analysis, and (b) whether higher scores on the scale correlated with positive outcomes in China. The final sample in this study consisted of 371 Chinese college students aged 17–23 years. The Full SCS and Brief SCS were both found to have a reasonable fitness, which also had satisfactory internal consistencies and a high correlation. Higher scores on the SCS correlated with higher self‐esteem, extraversion, better harmony in interpersonal relationships and an appropriate anger expression, less impulsiveness, and state and trait anger. The test–retest reliability was confirmed in two additional samples. Tangney's SCS could be used in China.